Study of the Extent of Dynamic Interaction of Certain Cationic Metal Ammine Complexes with Magnesium Molybdosilicate - Bhushan, B.; Seema (Asian Journal of Chemistry, 2010)
The rate of exchange of ammine complexes of CuIIl), Zn(II), Cd(II), Ni(II) and Co(II) in magnesium molybdosilicate has been studied at different concentrations of the exchanging ions. The rate of exchange is controlled by both the mechanisms, i.e., film diffusion and particle diffusion. The rate is controlled by film diffusion at lower concentration, whereas particle diffusion controls the rate process predominantly at and above 0.10 M concentration. It has been found that the rate of exchange of the above selected ammine complexes is characteristically dependent upon the ionic potential of the exchanging ion.